SYHNTHESIS OF CHITOSAN MODIFIED POLYURETHANE FOAM FOR ADSOPRTION OF MERCURY (II) IONS - Darmadi, Darmadi; M, Irfan; M, Iqhramullah; Marlina, Marlina; Lubis, Mirna Rahmah (Universitas Negeri Semarang, 2018)
Mercury from the traditional gold mining activities in Aceh Jaya Regency causes water source and thus residents are exposed to mercury metals. In organic and inorganic conditions, mercury is toxic to the human body, causes damage to the nerve system, kidney failure, heart failure, blood pressure disorders, and damage to the immune system. The problem of mercury contamination can be chemically solved in various ways. This research uses polyurethane foam to adsorb mercury from water. The adsorption and selectivity of polyurethane foam adsorption can be improved through modification with Chitosan. In this research, preheating temperature, glycerol and toluene di-isocyanate (TDI) compositions greatly affect the physical form of foam. The condition under which optimal glycerol composition used for synthesizing the polyurethane foams is 20% (w/w of mixture A). This glycerol composition results in polyurethane foams with an optimum ratio of the mixture A/TDI/distilled water of 2 : 1 : 1. The best adsorption is obtained with polyurethane foam added by 2.5% Chitosan. The optimum mercury adsorption 25% is resulted from the operating time of 60 minutes with adsorption capacity of 0.313 mg/g. For Chitosan modified polyurethane foam, research points out that the reaction is the second order reaction. The result concluded that the polymer has semi crystalline crystallization and melting temperatures.